Do Florida Medicaid Providers’ Barriers to HPV Vaccination Vary Based on VFC Program Participation? - Malo, Teri L. (2013)
OBJECTIVES: This study aimed to determine if physicians’ perceived barriers to HPV vaccination were associated with participation in the federal Vaccines for Children (VFC) program. METHODS: A sample of 800 Florida Medicaid providers was randomly selected from the Florida Medicaid Master Provider File. A cross-sectional study was conducted using a 27-item survey that included 13 potential barriers to immunizing Medicaid patients against HPV, including concerns about vaccine safety and efficacy, discussing sexuality, vaccinated teens practicing riskier sexual behaviors, cost and reimbursement, ensuring 3-dose series completion, and school attendance requirements associated with HPV vaccination. Pearson Chi-square tests were conducted to investigate differences between each barrier and VFC program participation. Data were analyzed for 449 physicians. RESULTS: Compared to non-VFC providers, VFC providers were significantly less likely to somewhat or strongly agree that the following were barriers to vaccination: the cost of stocking the HPV vaccine (p = 0.0011), lack of adequate reimbursement for HPV vaccination (p < 0.0001), and lack of timely reimbursement for HPV vaccination (p < 0.0001). After adjusting for provider specialty and number of years since completion of residency training, VFC status remained significantly associated with the barrier regarding lack of adequate reimbursement for vaccination such that non-VFC providers had a 2.6-fold (95% confidence interval, 1.1–5.8) greater odds of somewhat or strongly agreeing that this barrier applied to them. CONCLUSIONS: Increasing participation in the VFC program may decrease physicians’ cost-related barriers, which may increase the number of children vaccinated on time according to the recommended schedule.